English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

I need help on trying to at least start this problem.

2007-04-02 13:06:24 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

y' = x / sqrt( 1-4x^2) = (1/4) (1/2)(8x) / sqrt(1-4x^2)
so y = constant - (1/4) sqrt( 1-4x^2)
I dont think there any general method to bring out here ... you should just spot that y = sqrt(1-4x^2) would differentiate to -8x/sqrt(1-4x^2)

2007-04-02 13:12:57 · answer #1 · answered by hustolemyname 6 · 0 0

You need to integrate xdx/sqrt(1-4x^2)
Let u = 4x^2
Then du=8xdx --> xdx = du/8
So integral becomes 1/8integral [du/sqrt(1-u)]
= (1/8)[{2(-u-2)/3}{sqrt(1-u)}] +C
= [-(u+2)/12][sqrt(1-u)] +C
= [-(4x^2+2)][sqrt(1-4x^2] + C

2007-04-02 20:34:45 · answer #2 · answered by ironduke8159 7 · 0 0

Divide both sides by the square root:
dy/dx = x/sqr[1-4x^2]
dy = {x/sqr[1-4x^2]}dx
Integrate both sides

2007-04-02 20:09:51 · answer #3 · answered by kellenraid 6 · 0 0

rearange to get:

dy/dx = x/(1-2x) = x-0.5

therefore:

y = 1*x^0 -0

therefore:

y = 1

2007-04-02 20:12:37 · answer #4 · answered by pledger166 2 · 0 1

fedest.com, questions and answers